A resource-based learning approach to professional development: the case of the ACEE (Rhodes University Advanced Certificate in Environmental Education) - Agria Russo, Vladimir Kiluange (Rhodes University, Faculty of Education, Department of Education, 2004)
This interpretative case study derives and examines the characterising features of the resource-based learning approach used in the Rhodes University Advanced Certificate in Environmental Education (ACEE), particularly in Module 1 (Environment and Environmental Issues) and Module 3 (Contemporary Environmental Issues). The study explores processes of resource-based learning through the analysis of three individual case stories of participants' experience in adaptive use of learning support materials in different work contexts. It discusses the relationship between thematic categories related to participants' experience of assignment work, and course design and course implementation. This study indicates that resource-based learning processes in the ACEE involve curriculum deliberation and the use of resource packs in supporting participants' practice. It also indicates that the ACEE's practice-based orientation to workplace-based assignments plays an important role in supporting the adaptive use of learning support materials, encouraging lifelong learning and developing applied competence. It highlights the significance of reflexive narration of practice in improving course participants' educational practice. A diagrammatic representation of the unfolding and intermeshed characterising features of resource-based learning is presented. The study argues that resource-based learning in the ACEE appears to create possibilities for the course participants to become scaffolders and co-constructors of their own learning. It notes that resource-based learning can enable course participants to take ownership of their educational and workplace needs, and to develop skills and competences necessary to respond to environmental issues and risks in southern Africa. This study examines the potential that the reflexive narration of practice has in supporting course participants to engage in better ways of doing things in their workplace-based contexts. This study provides some recommendations to enhance the Advanced Certificate in Environmental Education as well as some 'fuzzy generalisations' that might guide the Southern African Development Community (SADC) Regional Environmental Education Programme (REEP) in the development and adaptation of professional development courses in southern Africa.
Keywords: Rhodes University Advanced Certificate in Environmental Education; Teaching -- Aids and devices -- South Africa; Environmental education -- South Africa